2016
DOI: 10.2323/jgam.62.98
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sirtuin and its target as the ribosomal protein S4 in <i>Lactobacillus paracasei</i>

Abstract: Sirtuin is a protein with an enzymatic activity of NAD + -dependent protein deacetylation. It was first identified in yeast and its homologous genes have been widely found in various organisms. In bacteria, sirtuin gene was first described as cobB, encoding a cobalamin processing enzyme; and later its potential involvement in regulating acetylation levels of metabolic enzymes, transcription factors, chemotactic proteins and others have been reported. In order to study its physiological relevance in probiotic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous finding in L. paracasei BL23 showed that a 28 kDa protein had increased its acetylation level with treatment of nicotinamide, a known sirtuin inhibitor in vivo, and had decreased its acetylation level upon supplementation of purified recombinant LpSirA with NAD + in vitro, indicating this protein as LpSirA target. This previous study also revealed one of the sirtuin target proteins in this cell was 30S ribosomal protein S4, suggesting role of LpSirA in protein synthesis [14]. Another study of note is the global acetylome analysis of E. coli proteins which showed that CobB mutation affected the acetylation levels of numerous proteins including those involved in protein synthesis (highly statistically significantly shorter and longer in comparison with the wild-type.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Previous finding in L. paracasei BL23 showed that a 28 kDa protein had increased its acetylation level with treatment of nicotinamide, a known sirtuin inhibitor in vivo, and had decreased its acetylation level upon supplementation of purified recombinant LpSirA with NAD + in vitro, indicating this protein as LpSirA target. This previous study also revealed one of the sirtuin target proteins in this cell was 30S ribosomal protein S4, suggesting role of LpSirA in protein synthesis [14]. Another study of note is the global acetylome analysis of E. coli proteins which showed that CobB mutation affected the acetylation levels of numerous proteins including those involved in protein synthesis (highly statistically significantly shorter and longer in comparison with the wild-type.…”
Section: Discussionmentioning
confidence: 59%
“…Cells were washed twice with PBS containing 0.1% (w/v) Tween 20 and blocked in PBS containing 2% (w/v) BSA, 0.3% (w/v) Triton X-100 and 0.1% (w/v) NaN 3 for 10 min. Cells were probed with a rabbit anti-LpSirA antibody [14] in PBS containing 2% (w/v) BSA, 0.3% (w/v) Triton X-100 and 0.1% (w/v) NaN 3 (1:250 dilution) for 1 h at 37 °C. Following four washes with PBS containing 0.1% (w/v) Tween 20, cells…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Some examples are the proteins Ku and LigD, components of the non-homologous end-joining (NHEJ) system from M. smegmatis and M. tuberculosis or the E. coli RNAse II (Li et al, 2011;Song et al, 2016). Finally, sirtuins have also been related to translation through E. coli alanyl-tRNA synthetase and Lactobacillus paracasei ribosomal S4 30S protein deacetylation (Atarashi et al, 2016;Torres-Barredo et al, 2018;Umehara et al, 2018). The elongation factor Tu from B. subtilis, TufA, is also regulated by reversible acetylation.…”
Section: Sirtuins In Transcription and Translation Processesmentioning
confidence: 99%